PCB anti-diffusion agent, preparation method and application thereof
Patent Information
- Application Number
- CN202411076866.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-08-07
AI Technical Summary
但PCB喷墨打印防扩散剂用量大(2%-3%),成本较高,此外萘磺酸衍生物的使用可能会造成铜面腐蚀,影响附着力、耐酸碱等性能
[0042](1)制备简单:本发明只需简单搅拌混合即可,且对PCB基材铜面和FR4面均有效果。现有技术包含有机硅聚合物的键合剂的表面处理液,制备过程中有无机盐的生成,需通过蒸除部分溶剂、过滤的方法除去无机盐;而包含6-18碳原子的烷基胺及其盐的表面处理剂虽然也仅需简单搅拌混合即可,但其对FR4面无效果;
Smart Images

Figure BDA0004982562160000071 
Figure BDA0004982562160000081 
Figure BDA0004982562160000091
Abstract
Description
Technical Field
[0001] This invention relates to the field of printed circuit board manufacturing technology, and more specifically, to a PCB anti-diffusion agent, its preparation method, and its application. Background Technology
[0002] Because copper has a high surface energy, and solder resist ink usually needs to be sandblasted or micro-etched before printing to ensure good adhesion between the solder resist ink and the printed circuit board (PCB) substrate, the above two reasons cause the solder resist ink to easily spread at the boundary after printing. This not only results in poor printing accuracy, but also makes the edge of the solder resist ink thinner, leading to an increase in product defect rate.
[0003] Existing technologies primarily employ bonding agents to inhibit the diffusion of solder resist ink. Bonding agents, also known as coupling agents, are effective surface treatment agents that enhance surface adhesion. For example, the invention patent with application number 202010572697.5 uses a bonding agent containing an organosilicon polymer to treat a roughened substrate, forming a hydrophobic film layer on the substrate surface. This results in a surface where the contact angle between the solder resist ink and the copper surface is 72°, preventing diffusion after printing and preventing ink loss during nickel-gold and tin plating. This organosilicon polymer contains alkane groups with 1-2 carbon atoms, aliphatic groups containing thiols or aromatic groups containing thiols, aliphatic groups containing aromatic amines or nitrogen-containing heterocycles, and aliphatic groups (containing one of vinyl, acrylate, and methacrylate groups). The alkyl groups provide hydrophobicity, while the silanol, amino, and thiol groups complex with the copper surface to reduce surface energy. Furthermore, the amino, thiol, and aliphatic groups can react with components in the solder resist ink to form bonds, improving the adhesion between the solder resist ink and the substrate. However, the preparation process of this patent involves the generation of inorganic salts, which need to be removed by first evaporating part of the solvent and then filtering. The preparation process is complicated, and it uses many components and a large amount of bonding agent (2%-3%), resulting in high costs.
[0004] The invention patent with application number 202210765329.1 uses an anti-diffusion liquid containing a diepoxyphenyl thiol compound bonding agent, a disulfonic acid reinforcing agent, an alkylbenzene glycol wetting agent, a thiazolidinone accelerator, and a dihydroxybenzophenone stabilizer to treat a roughened PCB substrate, forming an organic layer on the substrate surface. This organic layer reacts chemically with the solder resist ink, reducing the surface energy of the substrate and preventing ink droplets from spreading on the substrate, resulting in a surface where the contact angle between the solder resist ink and the PCB substrate is 80°-85.5°, and the ink does not spread after printing. However, the patent uses a large amount of bonding agent (3%-8%), resulting in high cost, and the use of thiols and disulfonic acids may cause copper surface corrosion, affecting adhesion, acid and alkali resistance, and other properties.
[0005] Patent application CN202410434303.8 discloses a PCB inkjet printing anti-diffusion agent comprising a hydrophobic agent (a mixture of a dicyclohexane crown ether derivative and an aminonaphthalene sulfonic acid derivative), a wetting agent (a betaine derivative), a stabilizer (a diaminobenzoate methyl ester derivative), and a cosolvent (a piperidinol derivative). This anti-diffusion agent can form an organic layer on the copper surface and substrate surface of the circuit board, effectively preventing the ink from spreading on the copper surface and substrate surface. However, the amount of PCB inkjet printing anti-diffusion agent used is large (2%-3%), resulting in high cost. In addition, the use of naphthalene sulfonic acid derivatives may cause copper surface corrosion, affecting adhesion, acid and alkali resistance, and other properties.
[0006] The invention patent with application number US16753986, "Method for Producing Film Formation Substrate, Film Formation Substrate, and Surface Treatment Agent," uses a surface treatment agent containing alkylamines and their salts, which contain 6-18 carbon atoms, to treat ultra-roughened copper surfaces. The amino groups complex with the copper surface to reduce the surface energy, while the alkyl groups provide hydrophobicity, thereby obtaining a surface with a contact angle of 10-120° between the solder resist ink and the copper surface. This effectively inhibits the diffusion and leakage of the solder resist ink. However, this surface treatment agent is only effective on ultra-roughened copper surfaces.
[0007] In addition, all four existing technologies mentioned above use an immersion process, which requires a water washing process after immersing in the anti-diffusion surface treatment agent, making the process lengthy. Summary of the Invention
[0008] One of the objectives of this invention is to provide a PCB anti-diffusion agent for spraying to prevent the diffusion and leakage of solder resist ink, which allows the PCB to be sprayed with solder resist ink without water washing after treatment.
[0009] A PCB anti-diffusion agent, the raw materials of which include the following components in parts by weight: 0.1-5 parts aminosilane coupling agent, 0.1-5 parts alkylsilane coupling agent, 0.1-5 parts acid solution and 970-999.7 parts solvent;
[0010] The molar ratio of the amino group in the aminosilane coupling agent to the acid in the acid solution is 1:(1.5-2.5).
[0011] In one preferred embodiment, the molar ratio of the aminosilane coupling agent to the alkylsilane coupling agent is (1-7):(3-9).
[0012] If the proportion of aminosilane coupling agent is too high, the contact angle decreases, and the solder resist ink diffuses. Therefore, the molar ratio of n-octyltrimethoxysilane to γ-aminoethylaminopropyltrimethoxysilane should be 9:1-3:7.
[0013] In one preferred embodiment, the solvent is water, a water-soluble alcohol, or a mixture thereof.
[0014] In one preferred embodiment, the water-soluble alcohol is one or more of n-propanol, isopropanol, ethanol, or methanol.
[0015] In the PCB anti-diffusion agent of this invention, the aminosilane coupling agent hydrolyzes in the solvent to form silanol, which bonds to the substrate surface (copper surface or FR4 surface), reducing surface energy. The amino group complexes with the hydroxyl groups on the substrate surface, further reducing surface energy, and can also react with components in the solder resist ink to form bonds, improving the adhesion between the solder resist ink and the substrate. Furthermore, it can be neutralized with glacial acetic acid to improve the shelf life. Therefore, the molar ratio of amino to acid in the aminosilane coupling agent is 1:(1.5-2.5). Within this range, silanol condenses during storage, shortening the shelf life. Too much or too little amino group will significantly affect the shelf life. Too much amino group results in an alkaline solution; too little amino group results in an acidic solution; both acids and alkalis exacerbate condensation, thus shortening the shelf life. The alkylsilane coupling agent hydrolyzes in the solvent under the action of acid to form silanol, which bonds to the substrate surface (copper surface, FR4 surface), reducing surface energy. On the other hand, the hydrophobic properties of the alkyl chain further improve the contact angle between the solder resist ink and the substrate surface. Aminosilane coupling agents hydrolyze in solvents to form silanols, which then bond to the substrate surface (copper surface, FR4 surface), reducing surface energy. Simultaneously, the amino group can complex with copper, improving adhesion to the copper surface. Aminosilane coupling agents can also condense with alkylsilane coupling agents to form films, achieving substrate surface modification and synergistically improving the anti-diffusion effect on the substrate surface. Glacial acetic acid promotes the hydrolysis of alkylsilane coupling agents to silanols, which volatilize during drying, thus avoiding adverse effects on subsequent processes. The solvent acts as a diluent, providing the necessary environment for the hydrolysis of silane coupling agents to silanols.
[0016] In one preferred embodiment, the aminosilane coupling agent contains at least one amino group and the number of carbon atoms in the aminosilane coupling agent is less than 12.
[0017] Aminosilane coupling agents have excessively long alkyl chains, resulting in poor adhesion.
[0018] In one preferred embodiment, the aminosilane coupling agent is a trimethoxy or triethoxysilane containing an alkyl chain with fewer than 12 carbon atoms.
[0019] Propoxysilane coupling agents have a lower hydrolysis rate than methoxy or ethoxy coupling agents. Butoxy and its hydrolysis products, butanol or long-chain alcohols with carbon chains longer than butane, are not miscible with water, leading to compatibility issues and deteriorating performance. Therefore, considering factors such as raw material availability, cost, compatibility, and processing performance, methoxy and ethoxy coupling agents are preferred.
[0020] In one preferred embodiment, the aminosilane coupling agent is one or more of γ-aminoethylaminopropyltrimethoxysilane, γ-aminoethylaminopropyltriethoxysilane, and γ-aminopropyltriethoxysilane.
[0021] In one preferred embodiment, the alkylsilane coupling agent is a trimethoxy or triethoxysilane containing an alkyl chain with 4-12 carbon atoms.
[0022] If the alkyl chain of an alkylsilane coupling agent has too few carbon atoms, the contact angle will be small, and the solder resist ink will diffuse. Conversely, if the alkyl chain has too many carbon atoms, the adhesion to the substrate will be poor. Therefore, the number of carbon atoms in the alkyl chain of an alkylsilane coupling agent should be 4-12.
[0023] In one preferred embodiment, the alkylsilane coupling agent is one or more of n-octyltrimethoxysilane, n-octyltriethoxysilane, butyltrimethoxysilane, butyltriethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, pentyltrimethoxysilane, heptyltrimethoxysilane, hexyltrimethoxysilane, and undecyltrimethoxysilane.
[0024] In one preferred embodiment, the acid solution is one or more of glacial acetic acid solution, formic acid solution, and propionic acid solution.
[0025] A volatile carboxylic acid, preferably a glacial acetic acid solution, is added to the reaction system to adjust the pH of the system to 6.5-8 for the hydrolysis of silane coupling agents.
[0026] In one preferred embodiment, the acid solution is an aqueous solution of an acid with a mass concentration of 5%-20%.
[0027] The second objective of this invention is to provide a simple and low-cost method for preparing a PCB anti-diffusion agent, comprising the following steps:
[0028] S1. Mix the alkylsilane coupling agent and a portion of the solvent, stir until homogeneous, and then add the acid solution dropwise while stirring. After the addition is complete, hydrolyze at 60-80℃ for 3-5 hours to obtain solution A.
[0029] S2. Mix the aminosilane coupling agent with another part of the solvent, stir evenly, and let stand to obtain solution B;
[0030] S3. Mix liquid A, liquid B and the remaining solvent, and stir until homogeneous to obtain the PCB anti-diffusion agent.
[0031] In one preferred embodiment, the mass concentration of alkylsilane coupling agent and aminosilane coupling agent in the PCB anti-diffusion agent is 0.01%-0.5%.
[0032] If the amount of silane coupling agent is too small, it will not achieve the desired anti-diffusion effect, resulting in severe diffusion of the solder resist ink; while if the amount of silane coupling agent is too large, the adhesion to the copper surface will deteriorate. Therefore, the mass concentration of alkylsilane coupling agents and aminosilane coupling agents should be 0.01%-0.5%.
[0033] This invention also claims a method for printing patterned solder resist on PCBs, comprising: spraying a PCB anti-diffusion agent onto the surface of a substrate, drying, printing solder resist ink, and curing to obtain an anti-diffusion PCB.
[0034] In one preferred embodiment, the coating thickness is 18-22 μm.
[0035] In one preferred embodiment, the drying temperature is 60-100°C.
[0036] In one preferred embodiment, curing includes: printing a substrate coated with solder resist ink under a UV LED lamp with an exposure energy of 800-1700 mJ / cm². 2 Then bake in an oven at 120-180℃ for 1-2 hours.
[0037] In one preferred embodiment, the printing rate is 200-600 mm / s.
[0038] This invention provides a PCB anti-diffusion agent that improves the contact angle of substrate surfaces (copper side, FR4 side), prevents solder resist ink diffusion and leakage, and is simple and low-cost to prepare. The PCB anti-diffusion agent provided by this invention differs from existing anti-diffusion surface treatment agents; it does not contain inorganic salts and can be applied using a spraying process, eliminating the need for rinsing after soaking in the surface treatment agent, allowing for direct drying.
[0039] In the PCB anti-diffusion agent of the present invention, aminosilane coupling agent and alkylsilane coupling agent can be condensed into a film, as shown in the schematic diagram below. Figure 1 As shown, the condensed nano-organic film achieves the purpose of substrate surface modification. Without condensation, the organic solvents in the solder resist ink would dissolve the aminosilane coupling agent and alkylsilane coupling agent, resulting in poor anti-diffusion effect. Simultaneously, the silanol and amino groups of the aminosilane coupling agent bond with the substrate, reducing surface energy, and the silanol groups of the alkylsilane coupling agent also bond with the substrate, further reducing surface energy. The hydrophobic properties of the alkyl chains further improve the contact angle between the solder resist ink and the substrate surface.
[0040] After treatment with the PCB anti-diffusion agent of this invention, the solder resist ink exhibits good adhesion to the substrate surface, excellent acid and alkali resistance, and no ink shedding during subsequent processing (such as electroless tinning, electroless nickel-gold bonding, and soldering). This enables precise printing of the solder resist ink and improves the product yield of the PCB solder resist process.
[0041] The beneficial effects of this invention are as follows:
[0042] (1) Simple preparation: This invention only requires simple stirring and mixing, and it is effective on both the copper surface and the FR4 surface of the PCB substrate. Existing surface treatment liquids containing organosilicon polymer bonding agents generate inorganic salts during the preparation process, which need to be removed by evaporation of some solvents and filtration. Although surface treatment agents containing alkylamines and their salts containing 6-18 carbon atoms also only require simple stirring and mixing, they are ineffective on the FR4 surface.
[0043] (2) Low cost: The effective ingredient dosage of the present invention is only 0.1%, which can significantly improve the contact angle of the solder resist ink on the copper surface and FR4 surface of the PCB substrate and effectively prevent the solder resist ink from spreading and leaking. In contrast, the effective ingredient dosage of the anti-diffusion surface treatment agent that is effective on both the copper surface and FR4 surface of the PCB substrate is more than 2%.
[0044] (3) No water washing required after anti-diffusion surface treatment: This reduces the need for water washing. Existing technologies introduce inorganic salts during preparation, requiring water washing after surface treatment.
[0045] (4) The anti-diffusion surface treatment agent has no adverse effects on subsequent processes and product performance: the solder resist ink has good adhesion to the substrate surface, good acid and alkali resistance, and no oil shedding during subsequent treatments (such as tin melting, nickel melting, soldering, etc.). Attached Figure Description
[0046] Figure 1 This is a schematic diagram of the structure of a membrane formed by the condensation of an aminosilane coupling agent and an alkylsilane coupling agent;
[0047] Figure 2 This is a diagram showing the contact angle between the solder resist ink and the copper surface after processing in Example 1.
[0048] Figure 3 This is a contact angle diagram between the solder resist ink and the FR4 surface after treatment in Example 1;
[0049] Figure 4 This is a diagram showing the shape of the solder resist ink on the copper surface after processing in Example 1;
[0050] Figure 5 This is a shape diagram of the solder resist ink on the FR4 surface after treatment in Example 1;
[0051] Figure 6 This is a diagram showing the contact angle between the solder resist ink and the copper surface after processing in Comparative Example 14.
[0052] Figure 7 This is a diagram showing the contact angle between the solder resist ink and the FR4 surface after treatment in Comparative Example 14.
[0053] Figure 8 This is a diagram showing the shape of the solder resist ink on the copper surface after treatment in Comparative Example 14.
[0054] Figure 9 This is a diagram showing the shape of the solder resist ink on the FR4 surface after treatment in Comparative Example 14. Detailed Implementation
[0055] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0056] It should be understood that, when used in this specification and the appended claims, the terms "comprising" and "including" indicate the presence of the described features, integrals, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integrals, steps, operations, elements, components and / or collections thereof.
[0057] Example 1
[0058] 1. Preparation of solution A: Dissolve 1.05 g (4.5 mmol) of n-octyltrimethoxysilane in 89 g of isopropanol, stir for 15 min, then add 10 g (16.7 mmol) of 10% acetic acid aqueous solution dropwise while stirring, continue stirring for 15 min, place it in a sealed container, and heat at 80 °C for 4 h for hydrolysis.
[0059] 2. Preparation of solution B: Dissolve 1 g (4.5 mmol) of γ-aminoethylaminopropyltrimethoxysilane in 99 g of isopropanol, stir for 15 min and let stand for 30 min.
[0060] 3. Mix 5g of liquid A, 5g of liquid B, and 90g of isopropanol until homogeneous to obtain the anti-diffusion surface treatment agent;
[0061] 4. Spray the anti-diffusion surface treatment agent obtained in step 3 onto the substrate surface (ultra-roughened copper surface, FR4 surface) with a thickness of 20μm.
[0062] 5. Place the substrate obtained in step 4 in an 80℃ oven to dry;
[0063] 6. Spray solder resist ink onto the substrate surface (ultra-roughened copper surface, FR4 surface) obtained in step 5;
[0064] 7. Place the substrate sprayed with solder resist ink obtained in step 6 under a UV LED lamp for curing, with an exposure energy of 1000mJ / cm2.
[0065] 8. Place the substrate with the surface-cured solder resist ink obtained in step 7 into an oven at 150°C and bake for 1 hour.
[0066] Example 2
[0067] The only difference between Example 2 and Example 1 is that n-octyltrimethoxysilane is replaced with n-octyltriethoxysilane.
[0068] Example 3
[0069] The only difference between Example 3 and Example 1 is that n-octyltrimethoxysilane is replaced with butyltrimethoxysilane.
[0070] Example 4
[0071] The only difference between Example 4 and Example 1 is that n-octyltrimethoxysilane is replaced with dodecyltrimethoxysilane.
[0072] Example 5
[0073] The only difference between Example 5 and Example 1 is that γ-aminoethylaminopropyltrimethoxysilane is replaced with γ-aminoethylaminopropyltriethoxysilane.
[0074] Example 6
[0075] The only difference between Example 6 and Example 5 is that γ-aminoethylaminopropyltriethoxysilane is replaced with γ-aminopropyltriethoxysilane.
[0076] Example 7
[0077] The only difference between Example 7 and Example 1 is that the molar ratio of alkylsilane coupling agent to aminosilane coupling agent is changed from 1:1 to 9:1, that is, step 3 is changed to stirring and mixing 9g of solution A, 1g of solution B, and 90g of isopropanol evenly.
[0078] Example 8
[0079] The only difference between Example 8 and Example 1 is that the ratio of alkylsilane coupling agent to aminosilane coupling agent is changed from 1:1 to 7:3, that is, step 3 is changed to stirring and mixing 7g of liquid A, 3g of liquid B, and 90g of isopropanol evenly.
[0080] Example 9
[0081] The only difference between Example 9 and Example 1 is that the ratio of alkylsilane coupling agent to aminosilane coupling agent is changed from 1:1 to 3:7, that is, step 3 is changed to stirring and mixing 3g of liquid A, 7g of liquid B, and 90g of isopropanol evenly.
[0082] Contact angle, adhesion, acid resistance, alkali resistance, and solderability were tested for Examples 1-9 and Comparative Examples 1-14. The performance testing methods are as follows:
[0083] 1. Contact Angle: The contact angle between the solder resist ink and the PCB substrate surface (copper side, FR4 side) is measured using a contact angle measuring instrument.
[0084] 2. Adhesion: The adhesion test shall be performed in accordance with GB / T 9286—1998 using the cross-cut test.
[0085] 3. Acid resistance: Immerse in 10 vol% H2SO4 for 30 min at room temperature, and test using the 3M tape cross-cut adhesion test.
[0086] 4. Alkali resistance: Immerse in 10 vol% NaOH for 30 minutes at room temperature, and test using the 3M tape cross-cut adhesion test.
[0087] 5. Solderability: According to IPC-TM-650 2.6.8, immerse in a 288℃ solder melting furnace for 10 seconds, three times.
[0088] The results are shown in Table 1.
[0089] Table 1 Performance results of Examples 1-9
[0090]
[0091]
[0092] As can be seen from Examples 1-9 in Table 1, the anti-diffusion surface treatment method for PCB solder resist ink of the present invention can effectively prevent the diffusion of ink on the substrate during the printing process. Furthermore, the solder resist ink treated with this surface treatment agent exhibits good adhesion, acid and alkali resistance, and solderability on the substrate surface. The anti-diffusion surface treatment agent of the present invention forms an organic layer on the substrate surface (copper surface, FR4 surface). This organic layer bonds with the substrate surface, reducing the surface energy of the substrate surface. In addition, the hydrophobic properties of the alkyl chain further improve the contact angle between the solder resist ink and the substrate surface, thereby preventing ink droplets from diffusing on the substrate. From the experimental data of Examples 1, 2, and 5 in Table 1, it can be seen that there is no significant difference in the surface contact angle and other properties of the solder resist ink treated with methoxysilane and ethoxysilane on the PCB substrate surface. The contact angle diagram of the solder resist ink treated in Example 1 with the copper surface is shown below. Figure 2 As shown, the angle is 81.5°. The contact angle diagram between the solder resist ink and the FR4 surface after treatment in Example 1 is shown below. Figure 3 As shown, the angle is 80.3°. The shape of the solder resist ink on the copper surface after treatment in Example 1 is shown in the figure. Figure 4 As shown, the shape of the solder resist ink on the FR4 surface after treatment in Example 1 is as follows. Figure 5 As shown. The results of other embodiments 2-9 are similar to those of the embodiments.
[0093] Comparative Example 1
[0094] The difference between Comparative Example 1 and Example 1 is that γ-aminoethylaminopropyltrimethoxysilane was not used; instead, 0.1% n-octyltrimethoxysilane was used to treat the substrate surface (copper side, FR4 side).
[0095] Comparative Example 2
[0096] The only difference between Comparative Example 2 and Example 1 is that n-octyltrimethoxysilane was not used; instead, 0.1% γ-aminoethylaminopropyltrimethoxysilane was used to treat the substrate surface (copper surface, FR4 surface).
[0097] Contact angle, adhesion, acid resistance, alkali resistance, and solderability were tested on Example 1 and Comparative Examples 1-2, and the results are shown in Table 2.
[0098] Table 2 Performance comparison of Example 1 and Comparative Examples 1-2
[0099]
[0100] From the experimental data of Example 1 and Comparative Example 1 in Table 2, it can be seen that the contact angle is significantly reduced when γ-aminoethylaminopropyltrimethoxysilane is missing. Furthermore, due to the lack of copolymerization with γ-aminoethylaminopropyltrimethoxysilane, the solder resist ink exhibits slight diffusion, and the adhesion to the copper surface deteriorates. γ-aminoethylaminopropyltrimethoxysilane hydrolyzes into silanol, which bonds to the substrate surface (copper surface, FR4 surface), reducing the surface energy. The amino group complexes with copper, reducing the surface energy, and can also react with components in the solder resist ink to form bonds, improving the adhesion between the solder resist ink and the copper surface.
[0101] From the experimental data of Example 1 and Comparative Example 2 in Table 2, it can be seen that the contact angle is significantly reduced when n-octyltrimethoxysilane is absent, and the solder resist ink exhibits severe diffusion due to the lack of copolymerization with n-octyltrimethoxysilane. The hydrolysis of n-octyltrimethoxysilane into silanol bonds to the substrate surface (copper surface, FR4 surface), reducing the surface energy. Simultaneously, the hydrophobic properties of the alkyl chain further improve the contact angle between the solder resist ink and the substrate surface.
[0102] Comparative Example 3
[0103] The only difference between Comparative Example 3 and Example 1 is that n-octyltrimethoxysilane is replaced with methyltrimethoxysilane.
[0104] Comparative Example 4
[0105] The only difference between Comparative Example 4 and Example 1 is that n-octyltrimethoxysilane is replaced with hexadecyltrimethoxysilane.
[0106] Contact angle, adhesion, acid resistance, alkali resistance, and solderability were tested on Examples 1, 3, and 4 and Comparative Examples 3 and 4, and the results are shown in Table 3.
[0107] Table 3 Performance comparison of Examples 1, 3, 4 and Comparative Examples 3, 4
[0108]
[0109] From the experimental data of Examples 1, 3, 4 and Comparative Examples 3, 4 in Table 3, it can be seen that: when the number of carbon atoms in the alkyl chain of the alkylsilane coupling agent is 1, the contact angle is small and the solder resist ink shows slight diffusion; when the number of carbon atoms in the alkyl chain is 16, the adhesion to the copper surface becomes poor. Therefore, the number of carbon atoms in the alkyl chain of the alkylsilane coupling agent should be 4-12.
[0110] Comparative Example 5
[0111] The only difference between Comparative Example 5 and Example 1 is that the ratio of alkylsilane coupling agent to aminosilane coupling agent is changed from 1:1 to 1:9, that is, step 3 is changed to stirring and mixing 1g of liquid A, 9g of liquid B, and 90g of isopropanol evenly.
[0112] Contact angle, adhesion, acid resistance, alkali resistance, and solderability were tested for Examples 1, 7, 8, 9 and Comparative Example 5, and the results are shown in Table 4.
[0113] Table 4 Performance comparison of Examples 1, 7, 8, 9 and Comparative Example 5
[0114]
[0115] From the experimental data of Examples 1, 7, 8, 9 and Comparative Examples 1, 2, 5 in Table 4, it can be seen that as the proportion of γ-aminoethylaminopropyltrimethoxysilane increases, the contact angle begins to decrease when the ratio of n-octyltrimethoxysilane to γ-aminoethylaminopropyltrimethoxysilane is 3:7, and then reaches 1:9, with slight diffusion of the solder resist ink. Therefore, the ratio of n-octyltrimethoxysilane to γ-aminoethylaminopropyltrimethoxysilane should be between 9:1 and 3:7.
[0116] Comparative Example 6
[0117] The only difference between Comparative Example 6 and Example 1 is that the mass concentration of alkylsilane coupling agent and aminosilane coupling agent is changed from 0.05% to 0.009%, that is, step 3 is changed to stirring and mixing 1g of liquid A, 1g of liquid B and 98g of isopropanol evenly.
[0118] Comparative Example 7
[0119] The only difference between Comparative Example 7 and Example 1 is that the mass concentration of alkylsilane coupling agent and aminosilane coupling agent is changed from 0.05% to 0.6%, that is, step 3 is changed to stirring and mixing 50g of liquid A and 50g of liquid B evenly.
[0120] Contact angle, adhesion, acid resistance, alkali resistance, and solderability were tested on Example 1 and Comparative Examples 6 and 7, and the results are shown in Table 5.
[0121] Table 5 Performance comparison of Example 1 and Comparative Examples 6 and 7
[0122]
[0123] From the experimental data of Example 1 and Comparative Examples 6 and 7 in Table 5, it can be seen that when the amount of silane coupling agent is too small, the anti-diffusion effect is not achieved and the solder resist ink diffuses severely; while when the amount of silane coupling agent is too large, the adhesion to the copper surface deteriorates. Therefore, the mass concentration of alkylsilane coupling agent and aminosilane coupling agent should be greater than 0.01% and less than 0.5%.
[0124] Comparative Example 8
[0125] The only difference between Comparative Example 8 and Example 1 is that n-octyltrimethoxysilane is replaced with γ-glycidoxypropyltrimethoxysilane.
[0126] Comparative Example 9
[0127] The only difference between Comparative Example 9 and Example 1 is that n-octyltrimethoxysilane is replaced with 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane.
[0128] Comparative Example 10
[0129] The only difference between Comparative Example 10 and Example 1 is that n-octyltrimethoxysilane is replaced with γ-methacryloyloxypropyltrimethoxysilane.
[0130] Comparative Example 11
[0131] The only difference between Comparative Example 11 and Comparative Example 1 is that n-octyltrimethoxysilane is replaced with γ-glycidoxypropyltrimethoxysilane.
[0132] Comparative Example 12
[0133] The only difference between Comparative Example 12 and Comparative Example 1 is that n-octyltrimethoxysilane is replaced with 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane.
[0134] Comparative Example 13
[0135] The only difference between Comparative Example 13 and Comparative Example 1 is that n-octyltrimethoxysilane is replaced with γ-methacryloyloxypropyltrimethoxysilane.
[0136] Comparative Example 14
[0137] Comparative Example 14 was a blank control group, which did not undergo anti-diffusion surface treatment.
[0138] Contact angle, adhesion, acid resistance, alkali resistance, and solderability were tested on Example 1 and Comparative Examples 1, 8-14, and the results are shown in Table 6.
[0139] Table 6 Performance comparison of Example 1 and Comparative Examples 8, 9, and 10
[0140]
[0141]
[0142] From the comparison of experimental data of Example 1 with Comparative Examples 8, 9, and 10, and the comparison of experimental data of Comparative Example 1 with Comparative Examples 11, 12, and 13 in Table 6, it can be concluded that: compared with hydrophilic epoxy and ester groups, alkylsilane coupling agents can significantly improve the contact angle between solder resist ink and the substrate surface through the hydrophobic properties of the alkyl chain, thereby inhibiting the diffusion of solder resist ink. The contact angle diagram between the solder resist ink and the copper surface in Example 14 is shown below. Figure 6 As shown, the angle is 8.0°. The contact angle diagram between the solder resist ink and the FR4 surface in Example 14 is shown below. Figure 7 As shown, the angle is 17.5°. The shape of the solder resist ink on the copper surface in Example 14 is shown in the figure. Figure 8 As shown, the shape of the solder resist ink in Example 14 on the FR4 surface is as follows. Figure 9 As shown.
[0143] In summary, after treatment with the PCB anti-diffusion agent of this invention, the solder resist ink exhibits excellent adhesion to the substrate surface, good acid and alkali resistance, and no ink shedding during subsequent processing (such as electroless tinning, electroless nickel-gold bonding, and soldering). This enables precise printing of the solder resist ink and improves the product yield of the PCB solder resist process.
[0144] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in the present invention, and these modifications or substitutions should all be covered within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A PCB anti-diffusion agent, characterized in that, Its raw materials consist of the following components in parts by weight: 0.1-5 parts aminosilane coupling agent, 0.1-5 parts alkylsilane coupling agent, 0.1-5 parts acid solution and 970-999.7 parts solvent; The molar ratio of the amino group in the aminosilane coupling agent to the acid in the acid solution is 1:(1.5-2.5); The molar ratio of the aminosilane coupling agent to the alkylsilane coupling agent is (1-7):(3-9); The aminosilane coupling agent contains at least one amino group, and the number of carbon atoms in the aminosilane coupling agent is less than 12; The acid solution is one or more of glacial acetic acid solution, formic acid solution, and propionic acid solution; The alkylsilane coupling agent is a trimethoxy or triethoxysilane containing an alkyl chain with 4-12 carbon atoms.
2. The PCB anti-diffusion agent according to claim 1, characterized in that, The solvent is water, a water-soluble alcohol, or a mixture thereof; the water-soluble alcohol is one or more of n-propanol, isopropanol, ethanol, or methanol.
3. The PCB anti-diffusion agent according to claim 1, characterized in that, The aminosilane coupling agent is a trimethoxy or triethoxysilane containing an alkyl chain with fewer than 12 carbon atoms.
4. The PCB anti-diffusion agent according to any one of claims 1-3, characterized in that, The acid solution is an aqueous solution of acid with a mass concentration of 5%-20%.
5. A method for preparing the PCB anti-diffusion agent according to any one of claims 1-4, characterized in that, Includes the following steps: S1. Mix the alkylsilane coupling agent and a portion of the solvent, stir until homogeneous, and then add the acid solution dropwise while stirring. After the addition is complete, hydrolyze at 60-80℃ for 3-5 hours to obtain solution A. S2. Mix the aminosilane coupling agent with another part of the solvent, stir evenly, and let stand to obtain solution B; S3. Mix liquid A, liquid B and the remaining solvent, and stir until homogeneous to obtain the PCB anti-diffusion agent.
6. The preparation method according to claim 5, characterized in that, In PCB anti-diffusion agents, the mass concentrations of alkylsilane coupling agents and aminosilane coupling agents are 0.01%-0.5%.
7. A method for printing patterned solder mask on a PCB, characterized in that, include: The PCB anti-diffusion agent according to any one of claims 1-4 is sprayed onto the surface of a substrate, dried, printed with solder resist ink, and cured to obtain an anti-diffusion PCB.
8. The method according to claim 7, characterized in that, curing include: The substrate coated with solder resist ink is printed under a UV LED lamp with an exposure energy of 800-1700 mJ / cm². 2 ; Then bake in an oven at 120-180℃ for 1-2 hours.
Citation Information
Patent Citations
PCB ink printing methods
CN111757609B
Printed circuit board (PCB) jet printing pattern resistance welding method
CN114845474A
PCB ink-jet printing anti-diffusion agent and preparation method and use method thereof
CN118290987A
Preparation method of functional coating
CN104927650A
Circuit resistance welding method of printed circuit board, pretreatment liquid used by circuit resistance welding method and circuit board
CN116017870A